Homeopathic Management of Anosmia (Homoeopathy for All, 2024)
Anosmia, defined as the loss of the  sense of smell, can significantly  impair an individual's quality of  life; however, its importance is  frequently underestimated. The  sense of smell is crucial for both the  appreciation of daily experiences,  such as food and nature, and for  the identification of potential  dangers, including gas leaks and  spoiled food. The failure to detect  these odors may jeopardize safety  and well-being. Anosmia can  arise from multiple etiologies,  such as viral infections, nasal  obstructions, or neurodegenerative  disorders, including Alzheimer's  and Parkinson's diseases.  The prevalence of smell loss  is significant among older  populations, with approximately  3.2% of U.S. adults over 40  affected, a statistic that increases  to 14–22% in individuals over  60. Anosmia is frequently  unrecognized, primarily due to the  absence of formal olfactory testing  in routine health examinations,  resulting in patients relying on  self-reporting of their symptoms.
Keywords: Anosmia; equilibrium; parosmia